A bycatch surprise: Scyllarus subarctus Crosnier, 1970 (Decapoda: Achelata: Scyllaridae) in the Mediterranean Sea. Issue 2 (13th April 2021) - Tanduo, Valentina; Osca, David; Crocetta, Fabio
Abstract: Scyllarus  Fabricius, 1775 includes nine species worldwide, three of which have been recorded from the Mediterranean Sea: S. arctus (Linnaeus, 1758 ), S. caparti  Holthuis, 1952, and S. pygmaeus  Bate, 1888 . A Scyllarus specimen not ascribable to any of the previous species was trawled in November 2020 in unconsolidated substrates in the Gulf of Naples, Italy. The sample was subsequently identified through an integrative taxonomic approach as Scyllarus subarctus  Crosnier, 1970, a species originally described from southern Angola (Eastern Atlantic Ocean) and apparently expanding northward along Western Africa. It is possible that this taxon may have been already present in the Mediterranean but went overlooked or undetected. Results obtained through molecular analyses underlined the necessity of an extensive update of the supraspecific taxonomy of scyllarids.